Epidemiology and pathophysiology of alcohol and breast cancer: update 2012 - Seitz, Helmut K. (Alcohol and alcoholism, 2012)
Abstract. Aims: To update epidemiological data on alcohol and breast cancer, with special emphasis on light alcohol consumption, and to review mechanisms of al